2022
DOI: 10.1111/1755-0998.13614
|View full text |Cite
|
Sign up to set email alerts
|

The genomic architecture of the passerine MHC region: High repeat content and contrasting evolutionary histories of single copy and tandemly duplicated MHC genes

Abstract: The major histocompatibility complex (MHC) is of central importance to the immune system, and an optimal MHC diversity is believed to maximize pathogen elimination.Birds show substantial variation in MHC diversity, ranging from few genes in most bird orders to very many genes in passerines. Our understanding of the evolutionary trajectories of the MHC in passerines is hampered by lack of data on genomic organization. Therefore, we assembled and annotated the MHC genomic region of the great reed warbler (Acroce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 86 publications
1
31
0
Order By: Relevance
“…Our analyses of allele segregation patterns indicated that MHC-I loci are tightly linked in the great reed warbler, with a recombination rate of 0.0030, corresponding to a genetic distance of 0.3 cM. A recent study confirmed this strong linkage by showing that MHC-I genes in the great reed warbler mainly are organized as tandemly duplicated genes within a small genomic region (Westerdahl et al, 2022).…”
Section: Discussionsupporting
confidence: 61%
“…Our analyses of allele segregation patterns indicated that MHC-I loci are tightly linked in the great reed warbler, with a recombination rate of 0.0030, corresponding to a genetic distance of 0.3 cM. A recent study confirmed this strong linkage by showing that MHC-I genes in the great reed warbler mainly are organized as tandemly duplicated genes within a small genomic region (Westerdahl et al, 2022).…”
Section: Discussionsupporting
confidence: 61%
“…Major Histocompatability Complex (MHC) diversity is altered in some avian species [ 17 ], which may affect susceptibility to disease [ 18 ]. We therefore compared MHC loci between black and mute swans.…”
Section: Resultsmentioning
confidence: 99%
“…MHC diversity is altered in some avian species 17 , which may affect susceptibility to disease 18 . We therefore compared MHC loci between black and mute swans.…”
Section: Black and Mute Swan Classical Mhc Class Loci Are Homologousmentioning
confidence: 99%